2013
DOI: 10.4103/0971-5851.113396
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced hypopituitarism in children with acute lymphoblastic leukemia

Abstract: Background:Acute Lymphoblastic Leukemia (ALL) is the most common malignancy among children for whom radiotherapy and chemotherapy are used for treatment. When hypothalamus-pituitary axis is exposed to radiotherapy, children's hormone level and quality of life are influenced. The aim of this study is to determine late effects of radiotherapy on hormonal level in these patients.Materials and Methods:In this study 27 children with ALL, who have been referred to Shahid Ramezanzadeh Radiation Oncology Center in Yaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…They recommended a reduction in the dose of radiotherapy in such patients wherever possible. [14] It has been reported that somatotroph hormone axis is more sensitive to radiation in children than in adults. Follin et al .…”
Section: Discussionmentioning
confidence: 99%
“…They recommended a reduction in the dose of radiotherapy in such patients wherever possible. [14] It has been reported that somatotroph hormone axis is more sensitive to radiation in children than in adults. Follin et al .…”
Section: Discussionmentioning
confidence: 99%
“…M. Mirouliaei и соавт. [7] оценили распространенность эндокринных последствий КО при остром лимфобластном лейкозе у детей. В исследование были включены 27 детей с острым лимфобластным лейкозом, получивших КО в дозе 18-24 Гр.…”
Section: распространенность и патогенез радиоиндуцированного дефицита...unclassified
“…The radiation of brain or neck tumors may affect the pituitary gland, thus leading to hypopituitarism 59 . In children with acute lymphoblastic leukemia, GHD seems to be the most common hormonal deficit after cranial radiation 60 . In adults, an increasing prevalence of hypopituitarism from 12.5% after 2 years up to 90% 15 years after radiation has been reported 61 .…”
Section: Acquired Hypopituitarism Due To Brain Traumamentioning
confidence: 99%